The development and validation of adventure based mental toughness inventory (AbMTI) for adventure based program in Malaysia - Mohd Shariman Shafie (Tanjong Malim, 2022)
The development and validation of adventure based mental toughness inventory (AbMTI) for adventure based program in Malaysia by Mohd Shariman Shafie